Distance visual acuity in air force pilots and student pilots when exposed to + Gz acceleration in human centrifuge - Randjelović, Danijela; Srećković, Sunčica; Šarenac Vulović, Tatjana; Petrović, Nenad (Vojnosanitetski pregled, 2022)
Background/Aim. High speeds that modern aircraft develop during take-off, flight and landing place an additional strain on the organ of vision. Owing to its considerable practical implementation in air combat, the effect of +Gz acceleration on the organ of vision is considered increasingly important for research. Substantial changes in visual functions may occur during high acceleration onset rates. However, it is important for a pilot to maintain visual acuity in order to be able to monitor new functional displays for rapid orientation, scan the configuration of terrain, display of weapons systems and enemy aircraft and deal with additional issues of the complexity of spatial orientation. The aim of the investigation was to establish whether distance visual acuity in air force pilots and student pilots is affected when exposed to +Gz acceleration. Меthods. The study was performed on a defined population consisting of 95 respondents from 21 to 45 years of age divided into two groups. The first group included 65 air force pilots and the second group comprised of 30 student pilots, all of whom were exposed to an acceleration of +5.5 Gz. The testing was performed in a human centrifuge, which mimics conditions of real Gz acceleration, in the Department of Biodynamics in Aero Medical Institute (Zemun, Serbia). We examined the obtained differences in distance visual acuity before and after exposure to acceleration. Results. After the testing, all respondents in the group of air force pilots had distance visual acuity of 1.0, while in the group of student pilots a statistically significant difference in distance visual acuity was observed after being exposed to +Gz acceleration. Conclusion. Transient changes in distant visual acuity were more pronounced in the group of student pilots in comparison with the changes in visual acuity in the air force pilots when exposed to the same acceleration values (+5Gz acceleration). Since change in distance visual acuity is the most sensitive physiological indicator when exposed to high acceleration, individual physiological pilot training in the human centrifuge increases tolerance to accelerations, which is important for flight safety in both peacetime and combat conditions.